The demography of tree species response to climate: sapling and canopy tree survival. Issue 2 (21st February 2017) - Canham, Charles D.; Murphy, Lora
Abstract: Traits affecting survival from seedling through adult stages are key elements of tree life histories, and it is widely assumed that variation in survival of adult trees plays an important role in the distribution of species along climate gradients. We use data from plots censused by the U.S. Forest Service Forest Inventory and Analysis program during the years 2000–2011 to quantify relationships between two key aspects of climate—mean annual temperature and growing season water deficit—and rates of sapling and canopy tree survival for the 50 most common tree species in the eastern United States. Our analyses include consideration of the effects of tree size, competition, and nitrogen deposition to avoid confounding effects and to provide context for the importance of variation in climate relative to other factors. Tree size and competitive effects, including the effect of tree size on sensitivity to competition, had the greatest impact on observed variation in survival for all of the species. Survival varied as a function of nitrogen deposition in 20 of the 50 species, and responses were stronger in saplings than in canopy trees. Despite clear sorting of the presence of the tree species along regional gradients of temperature and water deficit, there was only modest evidence that either sapling or canopy tree mortality varied systematically along those gradients. For 24 of the 50 species, the most parsimonious models did not include either temperature or water deficit variables. The exceptions to this were for several species of colder climates in which survival declined significantly in warmer climates. In 40 of the 50 species, there was no significant variation in survival as a function of either average growing season water deficit or the most extreme individual growing season water deficit during the 20 yr preceding the end of the census interval. The frequency of all but the most xeric of our study species declines at some point along a water deficit gradient. But it is seedling survival (reported in earlier work), rather than survival of saplings and canopy trees, that varies systematically along water deficit gradients.